2018
DOI: 10.3389/fimmu.2018.00096
|View full text |Cite
|
Sign up to set email alerts
|

Increased Interleukin-23 in Hashimoto’s Thyroiditis Disease Induces Autophagy Suppression and Reactive Oxygen Species Accumulation

Abstract: Hashimoto’s thyroiditis (HT) represents the most common organ-specific autoimmune disease. Inflammatory factors and reactive oxygen species (ROS) play detrimental roles during the pathogenesis of HT. In this study, we found that thyroid follicular cells (TFCs) from HT patients expressed an elevated level of interleukin-23 (IL-23), which contributed to autophagy suppression and ROS accumulation. Additionally, IL-23-induced autophagy suppression and ROS accumulation in human TFCs was attributed to AKT/mTOR/NF-κB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 44 publications
2
25
1
Order By: Relevance
“…Increasing evidence indicates the importance of autophagy in the pathogenesis and development of inflammation [58,59]. Previous work from our laboratory has found that the LC3B-II protein expression in TFC was sharply decreased in HT tissues compared with that of the healthy controls [23,24]. In this study, LC3B-II expression in TFC was significantly decreased following treatment with IL-1β and IFN-γ, suggesting that autophagy activity in TFC was suppressed under a Th1 cytokines environment.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Increasing evidence indicates the importance of autophagy in the pathogenesis and development of inflammation [58,59]. Previous work from our laboratory has found that the LC3B-II protein expression in TFC was sharply decreased in HT tissues compared with that of the healthy controls [23,24]. In this study, LC3B-II expression in TFC was significantly decreased following treatment with IL-1β and IFN-γ, suggesting that autophagy activity in TFC was suppressed under a Th1 cytokines environment.…”
Section: Discussionsupporting
confidence: 52%
“…Inhibition of autophagy may contribute to a bioenergetic shortage and favour oxidative reactions that trigger cell death characterized by hallmarks of apoptosis [22]. Autophagy activity is decreased and apoptosis level is increased in HT thyroids compared to in control thyroids [23,24]. Cav-1 has been associated with the apoptosis of thyroid cells [18].…”
mentioning
confidence: 99%
“…Therefore, these results as well as conclusions regarding the role of Th17 cells in GD pathogenesis must be interpreted with caution because the absolute number of patients with GD was only 8. Interestingly, Zheng et al showed an increase in IL-17 and RORγt mRNA expression in IL-23-stimulated cultured cells from GD patients when compared to those from controls and cultures without IL-23 [14]. Similar results were demonstrated in euthyroid GD patients, indicating an independent effect of thyroid hormone levels [29].…”
Section: Discussionmentioning
confidence: 73%
“…IL-37 exerts a protective role against oxidative stress and inflammation by inhibiting effects of Th1/Th17-mediated response [27]. Recently, another research group found the enhanced expression of IL-23 in the thyroid tissue of patients with HT when compared to controls [14]. Additionally, these authors demonstrated the accumulation of reactive oxygen species and the inhibition of autophagy in thyrocytes induced by increased IL-23.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation